2016
DOI: 10.1002/jclp.22323
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mindfulness and Posttraumatic Stress Disorder Symptoms Among Veterans Enrolled in Mindfulness-Based Stress Reduction

Abstract: These results extend previous research, provide preliminary support for changes in mindfulness as a viable mechanism of treatment, and have a number of potential practical and theoretical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 54 publications
6
39
0
2
Order By: Relevance
“…The current results shed light on why mindfulness‐ and acceptance‐based interventions may have utility for alleviating suffering and disability in people with PTSD. Findings from several studies suggest that mindfulness‐based treatments have several salutary benefits for traumatized populations, including civilians (Kelly & Garland, ) and veterans (Polusny et al., ; Stephenson et al., ). Taken together, current and past findings suggest that mindfulness‐based interventions have potential for assisting veterans in achieving meaningful functional recovery following warzone trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results shed light on why mindfulness‐ and acceptance‐based interventions may have utility for alleviating suffering and disability in people with PTSD. Findings from several studies suggest that mindfulness‐based treatments have several salutary benefits for traumatized populations, including civilians (Kelly & Garland, ) and veterans (Polusny et al., ; Stephenson et al., ). Taken together, current and past findings suggest that mindfulness‐based interventions have potential for assisting veterans in achieving meaningful functional recovery following warzone trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
“…When relied on in the long-term, these strategies become maladaptive and can contribute to PTSD (Hiraoka et al, 2015;Meyer, Morissette, Kimbrel, Kruse, & Gulliver, 2013;Orcutt, Bonanno, Hannan, & Miron, 2014). Increasingly, mental health providers are turning to mindfulness-and acceptance-based therapies, such as Acceptance and Commitment Therapy (ACT; Hayes, Strosahl, & Wilson, 2012;Hermann, Meyer, Schnurr, Batten, & Walser, 2016;Yadavaia, Hayes, & Vilardaga, 2014) and others (Neff & Germer, 2013;Polusny et al, 2015;Stephenson, Simpson, Martinez, & Kearney, 2016), that seek to bolster mindful awareness in an attempt to counteract these avoidance-based responses to trauma by promoting an adaptive and open stance.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to mechanisms of change, aggregate data from 2 studies by Kearney and colleagues 132,133 and 2 unpublished studies reported changes in nonreactivity and acting with awareness on the FFMQ to be most strongly associated with improvements in PTSD symptoms, particularly hyperarousal symptoms. 141 …”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 99%
“…However, although CPT reduces trauma‐related guilt for many individuals, some continue to report high levels of guilt despite successful treatment completion (Owens, Cox, & Chard, ). In recent years, a number of researchers (Felleman, Stewart, Simpson, Heppner, & Kearney, ; Kearney, McDermott, Malte, Martinez, & Simpson, , ; Kelly & Garland, ; King et al., ; Polusny et al., ; Stephenson, Simpson, Martinez, & Kearney, ) have explored the effectiveness of mindfulness‐based cognitive therapy (MBCT) and mindfulness‐based stress reduction (MBSR) in reducing PTSD symptom severity. Other treatment programs utilizing traditional evidence‐based treatments for PTSD also include various psychoeducation groups as an adjunct to treatment, some of which focus on teaching participants mindfulness skills (e.g., Owens, Walter, Chard, & Davis, ).…”
mentioning
confidence: 99%